Evaluation of the Performance of Online GPS/GNSS Data Processing Services for Monitoring the Land Deformations and Movements (Journal of Engineering, 2019)
In recent years, the Global Navigation Satellite Services (GNSS) technology has been frequently employed for monitoring the Earth crust deformation and movement. Such applications necessitate high positional accuracy that can be achieved through processing GPS/GNSS data with scientific software such as BERENSE, GAMIT, and GIPSY-OSIS. Nevertheless, these scientific softwares are sophisticated and have not been published as free open source software. Therefore, this study has been conducted to evaluate an alternative solution, GNSS online processing services, which may obtain this privilege freely. In this study, eight years of GNSS raw data for TEHN station, which located in Iran, have been downloaded from UNAVCO website on a daily basis. Furthermore, TEHN GNSS observations are processed with CSRS-PPP, which is based on Precise Point Positioning (PPP) algorithm, and OPUS, which is based on double difference (DD) algorithm, to compare between these two techniques in terms of station velocity estimation and Earth deformation. On the other hand, TEHN station solutions that produce via scientific software, GIPSY-OSIS, are obtained from Nevada Geodetic Laboratory (NGL) website for data validation. Eventually, the results show that both GNSS online processing services (CSRS-PPP and OPUS) are credibly efficient to estimate station velocities, while CSRS-PPP trustworthy service for monitoring the Earth deformation.